The Role of Parents in Foreign Language Teaching - Shohida Isakova (Peerian Journals Publishing, 2022)
The article describes the role of parents in the development of the child and mistakes in family upbringing, psychological problems in learning a foreign language, the psychological factors that determine the process of mastering the material. It also examines the impact of foreign language learning on the professional development of high school students, the history and theory of professional management, the problem of learning it in modern psychology, and the motivation for professional self-discovery in the process of learning a foreign language. Methods of study are given. Factors influencing the self-crying of schoolchildren are discussed.
Keywords: Language teaching; professional self-determination; motivation; technique